Association of The MCP-1 rs1024611 Polymorphism with Polycystic Ovary Syndrome in A Population of Indian Women: A Case-Control Study - Jijo Francis; Honey Sebastian; Saley Daniel; Leyon Varghese; Sareena Gilvaz; Ragitha Thenkattil Sankarankutty; Siji Susan George; Pulikkottil Raphael Varghese; Suresh Kumar Raveendran (International Journal of Fertility and Sterility)
Background: Polycystic ovary syndrome (PCOS) is one of the most prevalent endocrine conditions that significantlyimpact the life quality of reproductive-aged women. In the Indian population, its prevalence varies from 3.7 to 22.5%depending on ethnicity and diagnostic criteria. Chronic inflammation plays a pivotal role in PCOS pathogenesis.The monocyte chemoattractant protein-1 (MCP-1) is an important chemotactic factor for inflammatory response ofmonocytes. Genetic variations in the MCP-1 gene may modulate MCP-1 expression. Although the association of theMCP-1 promoter polymorphism (-2518A/G) was extensively studied in different inflammatory conditions, there isonly one report in PCOS conditions. Since no study was reported from the Indian population, we aimed to explore theassociation of the MCP-1 -2518A/G polymorphism (rs1024611) with PCOS.Materials and Methods: In this case-control study, to analyse the distribution and association of rs1024611 with PCOS,polymerase chain reaction-fragment length polymorphism (PCR-RFLP) analysis was carried out in 202 patients whoexhibited PCOS from menarche onwards or with higher severity of symptoms and 122 age-matched controls.Results: In our study, no significant correlation was observed in rs1024611 polymorphism with PCOS patients incomparison with control. In addition to this, we found no significant difference in the genotype and allele frequenciesbetween obese and non-obese PCOS patients.Conclusion: Our finding suggests that the MCP-1 -2518 A/G polymorphism has not been associated with PCOSpredisposition.